Pengembangan Aplikasi Pengelasan Berbasis Android sebagai Penunjang Belajar Siswa Kelas XI SMK Negeri Jawa Tengah - Rifqi, M. Irfan; Musyono, Ari Dwi Nur Indriawan; Rusiyanto, Rusiyanto; Kriswanto, Kriswanto (Panthera : Jurnal Ilmiah Pendidikan Sains dan Terapan, 2025)
This research aims to develop an Android-based learning media in the form of a welding simulation application to support practical learning in Vocational High Schools (SMK). The background of this research is limited practical facilities, limited learning time, and low student engagement in direct welding practice. The method used is Research and Development (R&D) with the 4D development model (Define, Design, Develop, and Disseminate). The application was developed and validated by four experts, consisting of two material experts and two media experts. The validation results by the material experts showed a feasibility level of 87.25%, categorized as "very feasible," while the validation results by the media experts obtained a score of 90.27%, categorized as "very feasible." Field trials were conducted on 24 eleventh-grade students at a vocational high school, and student responses showed a feasibility level of 89.41%. This application has been proven to improve understanding of basic welding concepts and skills independently and is an effective alternative to overcome the limitations of physical practice at school. This media is deemed feasible and has the potential for further development on other platforms as a technology-based vocational learning solution.